A new PDMS-b-PPO block copolymer membrane with novel non-perforated structure towards high flux for alcohol permselective pervaporation - W. Liu; H. X. Guo; S. L. Ji; H. J. Niu; J. R. Li (eXPRESS Polymer Letters, 2015)
The effective permselective pervaporation of alcohol is one of key technology for bio-alcohol industrial production. In this work, a new polydimethylsiloxane-block-polyphenylene oxide (PDMS-b-PPO) copolymer was first synthesized by a bridge reagent technique. Based on the copolymer structure confirmation, the asymmetric PDMS-b-PPO membrane was subsequently prepared by phase-inversion method in order to improve the anti-swelling capacity of PDMS. SEM observation indicated that the morphology of as-prepared membrane exhibited a ‘non-perforated’ structure, resulting from the phase-inversion and micro-phase separation of the PDMS-b-PPO copolymer in the membrane forming process. Furthermore, the structure changes of the membranes with different ratio of PDMS to PPO were investigated. This non-perforated structure in the membrane favored to reduce the diffusion resistance, together with the affinity of PDMS segment to alcohol during pervaporation process. Thus, the prepared PDMS-b-PPO membrane showed dramatically increased flux, in pervaporation separation of alcohol/water mixture. The flux of the PDMS-b-PPO membrane (PDMS content of 42.4%) can reach 3816.8 g/(m2h), along with 8.53 of separation factor in pervaporation of 5 wt% alcohol/water mixture (60°C). This work may provide a new strategy to design and fabricate new copolymer membranes for improving alcohol permselective pervaporation.